Smartphone assisted chromogenic sensing of halogenated solvents and monoaromatic hydrocarbons. (December 2021) - Debnath, Snehasish; Nair, Ratish R.; Bhattacharya, Arnab; Ghosh, Riya; Chatterjee, Pabitra B.
Abstract: Because of the frequent use in industry and commerce, each year million tons of organic solvents have been released to the environment without any prior treatment. Prolonged exposure of the hazardous solvents to humans have already triggered different health issues. As a result, development of off-laboratory and easy-to-handle analytical techniques to detect the harmful solvents are receiving paramount attention. The focus of this article is the development of naked eye observable colorimetric technique for the detection of halogenated solvents and monoaromatic hydrocarbons as well. Two divanadium(V) compounds (probes 1 and 2) were found to show distinct and instant color change to blue when a pinch of the probe is added to a large varieties of colorless solvents of monoaromatic hydrocarbons and halogenated organic compounds as well. The intense blue coloration is presumably due to the ligand-to-metal-charge-transfer (LMCT) and ligand-to-ligand-charge-transfer (LLCT) processes, as concluded from molecular orbital energy level diagrams generated from TD-DFT calculations. Practical applicability of the sensors has been tested by investigating the colorimetric response of the probes in organic solvent mixtures. We also have developed smartphone RGB color value based colorimetric sensing of halogenated and monocyclic aromatic hydrocarbon solvents in various nonpolar organic solvent mixtures, which might be useful for on-site naked eye sensing. Graphical abstract: Divanadium(V) compounds were found to function as highly efficient chromogenic sensors for environmentally hazardous halogenated as well as monoaromatic hydrocarbon solvents in pure and organic solvents mixtures, which can be performed by UV–vis technique and RGB color values. Image 1 Highlights: Naked eye observable unprecedented colorimetric sensing of various halogenated solvents and monocyclic aromatic hydrocarbons. Smartphone assisted colorimetric sensing of halogenated and monocyclic aromatic hydrocarbon solvents in organic solvent mixtures. Development of vanadium based chromogenic sensors for sensing hazardous organic solvents, even in solvent mixtures. Geometry optimized TD-DFT calculations confirmed that LMCT, LLCT, ILCT, and MLCT transitions are responsible for the colorimetric observed.